The Principal's Leadership Role in Improving the Quality of Education - Saputra, Ahmad Yudi; Sururuddin, Muhammad; Ramdan, Ahmad Yasar (Sumber Belajar Sejahtera, 2025)
This study aims to describe the leadership role of school principals: 1) As a manager in improving the quality of education; 2) As a leader in improving the quality of education; 3) Supporting and inhibiting factors in improving the quality of education and solutions to the inhibiting factors faced. The method used in this research is a qualitative approach with a case study research type. The data collection techniques in this study were interviews, observation and documentation. This research was conducted at SD Negeri 3 Masbagik Utara. The subjects of this research were the Principal and Teachers. The results obtained from this study are: (1) the principal's role as a manager in improving the quality of education is managing by planning, organizing, mobilizing, and evaluating; (2) the principal's role as a leader in improving the quality of education is monitoring, mediating teachers and students, disciplining, motivating, making innovations, liaising with outside parties, guiding students on an ongoing basis, fostering and improving teachers' abilities, and making decisions; (3) the supporting factors in improving the quality of education are the many relationships, support from other organizations, students are free to choose, facilitating teachers; while the inhibiting factors are conflicting systems with the office, frequent teacher turnover, the difficulty of implementing digital learning, sometimes constrained financing and lack of awareness of school community.